Academic Web Site Design and Academic Templates: Where Does the Library Fit In? - Peterson, Kate (Information Technology and Libraries, 2006)
Academic Web site design continues to evolve as colleges and universities are under increasing pressure to create a Web site that is both hip and professional looking. Many colleges and universities are using templates to unify the look and feel of their Web sites. Where does the library Web site fit into a comprehensive campus design scheme? The library Web site is unique due to the wide range of services and content available. Based on a poster session presented at the Twelfth Annual Association of College and Research Libraries conference in Minneapolis, Minnesota, April 2005, this paper explores the prevalence of university-wide academic templates on library Web sites and discusses factors libraries should consider in the future.